Hubungan Antara Indeks Massa Tubuh Dan Aktivitas Fisik Dengan Volume Oksigen Maksimum - Andriani, Rina, Isnaini Herawati , S.Fis., M.Sc (2016)
Background:Generally, obesity occur due to an imbalance between energy intake with the energy use. Excessive body fat levels can cause the decrease of VO2maxin a person. VO2max value is influenced by several factors, including BMI and physical activity. Research Objective: The purpose of the research was to determinethe relationship between body mass index (BMI), physical activity toward VO2max. Research Method:This research was an observational research since this research focused on to describe a circumstance or situation, with cross sectional approach. The population of this research were all people who stay in Nur Arief boarding house Rt 02 / Rw 01 Makamhaji with the total population of 55 people. Result: Results obtained from the regression statistic test of BMI and VO2max showed that BMI and VO2max has a negative relationship with tvalueof -2.539, Sig (p value) 0,016 smaller than 0.05 (0.016 <0.05). Results obtained from regression statistic test of physical activity and VO2max showed that physical activity and Vo2max has a positive relationship with tvalue of 3.920 with Sig (p value) of 0,000 is smaller than 0.05 (0.000 <0.05). And the correlation analysis between body mass index and physical activity with VO2max indicated that there is a strong relationship with rvalue is equal to 0.718, and Sig (p value) is 0.000. Conclusion: There is a significant correlation between body mass index and physical activity with VO2max ofpeople who stay in NurArief boarding house Rt 02 / Rw 01 Makamhaji. Keywords:Body mass index, physical activity, VO2max, Nur Arif boarding house Rt 02 / Rw 01 Makamhaji.